Malaria prevalence and long-lasting insecticidal net use in rural western Uganda: results of a cross-sectional survey conducted in an area of highly variable malaria transmission intensity - Cote, Claire M.; Goel, Varun; Muhindo, Rabbison; Baguma, Emmanuel; Ntaro, Moses; Shook‑Sa, Bonnie E.; Reyes, Raquel; Staedke, Sarah G.; Mulogo, Edgar M.; Boyce, Ross M. (Malaria journal, 2021)
Background: Long-lasting insecticidal nets (LLINs) remain a cornerstone of malaria control, but strategies to sustain universal coverage and high rates of use are not well-defined. A more complete understanding of context-specific factors, including transmission intensity and access to health facilities, may inform sub-district distribution approaches and tailored messaging campaigns. Methods: A cross-sectional survey of 2190 households was conducted in a single sub-county of western Uganda that experiences highly variable malaria transmission intensity. The survey was carried out approximately 3 years after the most recent mass distribution campaign. At each household, study staff documented reported LLIN use and source among children 2 to 10 years of age and performed a malaria rapid diagnostic test. Elevation and distance to the nearest health facility was estimated for each household. Associations between parasite prevalence and LLIN use were estimated from log binomial regression models with elevation and distance to clinic being the primary variables of interest. Results: Overall, 6.8% (148 of 2170) of children age 2–10 years of age had a positive RDT result, yielding a weighted estimate of 5.8% (95% confidence interval [CI] 5.4–6.2%). There was substantial variability in the positivity rates among villages, with the highest elevation villages having lower prevalence than lowest-elevation villages (p<001). Only 64.7% (95% CI 64.0–65.5%) of children were reported to have slept under a LLIN the previous night. Compared to those living < 1KM from a health centre, households at > 2KM were less likely to report the child sleeping under a LLIN (RR 0.86, 95% CI 0.83–0.89, P<.001). Households located farther from a health centre received a higher proportion of LLINs from government distributions compared to households living closer to health centres. Conclusion: LLIN use and sourcing was correlated with household elevation and estimated distance to the nearest health facility. The findings suggest that current facility-based distribution strategies are limited in their reach. More frequent mass distribution campaigns and complementary approaches are likely required to maintain universal LLIN coverage and high rates of use among children in rural Uganda.
Keywords: Malaria; Plasmodium; Mosquito nets; Insecticide-treated bed nets; Uganda